HUBUNGAN POSTPARTUM BLUES, DAN EFIKASI DIRI DENGAN PELAKSANAAN SENAM NIFAS DI POLINDES TUNAS BUNDA DESA MANDDELEN KECAMATAN LENTENG TAHUN 2015 - Ratna Indriyani (Wiraraja Medika : Jurnal Kesehatan, 2015)
purpose is to expedite the process of involution. Postpartum blues and self efficacy amongthe factors that affect the implementation of puerperal gymnastics. This study aimed topostpartum blues relationship, and self efficacy with the implementation of puerperalpuerperal gymnastics in UPT PuskesmasLenteng.Design Cross-sectional study. Independent variables postpartum blues, self-efficacy andthe dependent variable implementation of puerperal gymnastics on 31 respondents.The onemonthstudy period UPT PuskesmasLenteng.Totalnpopulasi samplingtechniques.Instruments questionnaire. SPSS statistical test Chi-square α (0.05).Results of research most likely to experience postpartum blues (54.8%), most have apositive self-efficacy (58.1%), and most of the implementation of puerperal gymnastics isnegative (61.3%).Statistical test results postpartum blues with the implementation of puerperal gymnasticsobtained  value = 0,008 with a value of α = 0.05 and OR = 8.400, so  (0,008) <α (0.05), H0is rejected means no relationship with postpartum blues implementation puerperalgymnastics , OR = 8.400 means 8.400 times postpartum blues gymnastics determine theimplementation of parturition. Statistical test result with the implementation of self-efficacy isobtained puerperal gymnastics  value = 0,003 with a value of α = 0.05 and OR = 11.250, so (0,003) <α (0.05), H0 is rejected means that there is a connection with the implementationof self-efficacy gymnastics parturition , OR = 11.250 11.250 times mean self-efficacydetermine the implementation of puerperal gymnastics.Efforts to improve the implementation of gymnastics parturition through the elimination ofpostpartum blues and increase self-efficacy should be integrated in the ANC, INC, to PNC.Keywords : Postpartum Blues, Self-Efficacy, The Implementation Of PuerperalGymnastics